Spectral determination of μa, μs and g from single and multiple scattering signals with one optically thick sample. (April 2020) - Tian, Peng; Mutisya, Stephen M.; Jin, Jiahong; Zheng, Shuai; Lu, Jun Q.; Hu, Xin-Hua
Highlights: A new and robust method for determination of absorption coefficient μ a, scattering coefficient μs and anisotropy factor g has been developed without integrating spheres based on the radiative transfer (RT) theory. The RT parameters are determined from the measured signals of forward transmittance dominated by light of single scattering and non-hemispherical diffuse reflectance and transmittance dominated by light of multiple scattering. An inverse algorithm based on GPU executed Monte Carlo simulations has been developed to rapidly obtain the RT parameters from the measured signals. The new method has been validated against the Mie theory with different sphere suspension samples in a spectral region of 460–1000 nm. Uniqueness of the inverse solutions has been proved at selected wavelengths. Abstract: Development of robust and easy-to-implement methods for quantitative turbidity characterization by inherent properties of absorption and scattering can have wide applications. We report a new method for multiparameter characterization of turbid samples with three photodiodes based on the radiative transfer (RT) theory. Instead of acquiring collimated transmittance by spatial filtering and scattered light signals by integrating spheres, the method determines RT parameters from forward transmittance dominated by light of single scattering and non-hemispherical diffuse reflectance and transmittance dominated by light of multiple scattering. A Monte Carlo based inverse algorithm has been developed to rapidly obtain absorption coefficient μ a, scattering coefficient μs and anisotropy factor g at multiple wavelengths. The method has been validated with different sphere suspensions against the Mie theory. RT parameters for suspensions of spheres of 0.966 µm and 11 µm in nominal diameter values has been determined in a spectral region of 460–1000 nm and the uniqueness of the inverse solutions has been proved at selected wavelengths.